Ana o 1 and Ana o 2 cashew allergens share cross‐reactive CD4+ T cell epitopes with other tree nuts. Issue 6 (June 2016) - Archila, L. D.; Chow, I‐T.; McGinty, J. W.; Renand, A.; Jeong, D.; Robinson, D.; Farrington, M. L.; Kwok, W. W.
Summary: Background: Allergies to cashew are increasing in prevalence, with clinical symptoms ranging from oral pruritus to fatal anaphylactic reaction. Yet, cashew‐specific T cell epitopes and T cell cross‐reactivity amongst cashew and other tree nut allergens in humans remain uncharacterized. Objectives: In this study, we characterized cashew‐specific T cell responses in cashew‐allergic subjects and examined cross‐reactivity of these cashew‐specific cells towards other tree nut allergens. Methods: CD154 up‐regulation assay was used to determine immunodominance hierarchy among cashew major allergens at the T cell level. The phenotype, magnitude and functionality of cashew‐specific T cells were determined by utilizing ex vivo staining with MHC class II tetramers. Dual tetramer staining and proliferation experiments were used to determine cross‐reactivity to other tree nuts. Results: CD4 + T cell responses were directed towards cashew allergens Ana o 1 and Ana o 2. Multiple Ana o 1 and Ana o 2 T cell epitopes were then identified. These epitopes elicited either TH 2 or TH 2/TH 17 responses in allergic subjects, which were either cashew unique epitope or cross‐reactive epitopes. For clones that recognized the cross‐reactive epitope, T cell clones responded robustly to cashew, hazelnut and/or pistachio but not to walnut. Conclusions: Phylogenetically diverse tree nut allergens can activate cashew‐reactive T cells and elicit a TH 2‐type response at an epitope‐specific level. Clinical relevance: Lack of cross‐reactivity between walnut and cashew suggests that cashew peptide immunotherapy approach may not be most effective for walnut.